The effect of curcumin on anthropometric indices, blood pressure, lipid profiles, fasting blood glucose, liver enzymes, fibrosis, and steatosis in non-alcoholic fatty livers - Safari, Zahra; Bagherniya, Mohammad; Khoram, Ziba; Ebrahimi Varzaneh, Amrollah; Heidari, Zahra; Sahebkar, Amirhossein; Askari, Gholamreza (Frontiers in Nutrition, 2023)
Background: Non-alcoholic fatty liver disease (NAFLD) is the most common form of liver disease. Curcumin is a natural polyphenol that may be effective against liver steatosis and steatohepatitis. This study aimed to evaluate the effects of phytosomal curcumin on lipid profile, fasting blood sugar, anthropometric indices, liver enzymes, fibrosis and steatosis in non-alcoholic fatty liver patients. Methods: The participants were randomized to the curcumin-phosphatidylserine phytosomal receiving group and the placebo receiving group and were followed for 12 weeks. Data on anthropometric indices, lipid profile, blood glucose, blood pressure, liver enzymes as well as hepatic steatosis and fibrosis were collected at the beginning and the end of the trial. Results: Twelve weeks of supplementation with phytosomal curcumin significantly reduced fibrosis and steatosis compared with the placebo group (P<0.05). Phytosomal curcumin also led to a significant reduction in waist circumference and blood pressure compared with the placebo group (P<0.05). There was no significant difference between phytosomal curcumin and placebo groups in terms of changes in weight, body mass index, fasting blood glucose, liver enzymes, and lipid profile. Conclusion: Curcumin, at a dose of 250 mg per day, might be effective in the treatment of patients with NAFLD. Further studies are warranted to confirm these findings and to discover the underlying mechanisms.